PENGARUH CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Saifi, Muhammad (FIA UB, 2019)
This study examines the effect of corporate governance and ownership structure on the company's financial performance. Good corporate governance is proxyed by the proportion of independent commissioners, while the ownership structure is proxyed by the proportion of institutional and managerial ownership. Financial performance indicators are measured by Return on Equity (ROE) and Return on Assets (ROA). The sample used was 22 companies from a population of 54 property companies and public real estate that were publicly traded on the Indonesia Stock Exchange and obtained a total of 110 observations for the period 2011-2015. The sample is determined using the purposive sampling method. This study uses multiple regression analysis and is processed using SPSS. The results showed that there was a significant negative effect between the proportion of independent commissioners and institutional ownership of financial performance as measured by ROE. However, managerial ownership was found not to have a significant effect on financial performance as measured by ROE. Other results indicate that the proportion of independent commissioners, institutional ownership, and managerial ownership has a positive and significant effect on financial performance measured using ROA.Â